1999
DOI: 10.1021/jp990486+
|View full text |Cite
|
Sign up to set email alerts
|

Front Dynamics during Diffusion-Limited Corrosion of Ramified Electrodeposits

Abstract: Experiments on the diffusion-limited corrosion of porous copper clusters in thin gap cells containing cupric chloride are reported. By carefully comparing corrosion front velocities and concentration profiles obtained by phase-shift interferometry with theoretical predictions, it is demonstrated that this process is well-described by a one-dimensional mean-field model for the generic reaction A + B (static) → C (inert) with only diffusing reactant (cupric chloride) and one static reactant (copper) reacting to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 59 publications
3
39
0
Order By: Relevance
“…Me ^^ Me n+ + ne (12) nFe 3+ + ne nFe 2+ (13) The Fe 2+ ions formed in the course of corrosion are spontaneously reoxidized to Fe 3+ , while in agreement with Eq. (7), an equivalent amount of oxygen is ionized.…”
Section: The Corrosion Effect Of Fechsupporting
confidence: 67%
See 1 more Smart Citation
“…Me ^^ Me n+ + ne (12) nFe 3+ + ne nFe 2+ (13) The Fe 2+ ions formed in the course of corrosion are spontaneously reoxidized to Fe 3+ , while in agreement with Eq. (7), an equivalent amount of oxygen is ionized.…”
Section: The Corrosion Effect Of Fechsupporting
confidence: 67%
“…In the fabrication of integrated circuits, in the activation of atmospheric oxygen both redox systems are effective and this results in the etching of surplus copper.In the case of metal corrosion,(12) and the process Cu 2+ (C1") + e Cu + (C1") In the fabrication of integrated circuits, in the activation of atmospheric oxygen both redox systems are effective and this results in the etching of surplus copper.In the case of metal corrosion,(12) and the process Cu 2+ (C1") + e Cu + (C1")…”
mentioning
confidence: 99%
“…6. These results may be used to infer reaction orders and perhaps even kinetic constants in diffusion-limited corrosion experiments from transient decay measurements of the reaction-rate density in the diffusion layer [3].…”
Section: The Decay Time When N =mentioning
confidence: 99%
“…Experiments by Leger et al (1999), examining front dynamics during diffusion-limited corrosion of ramified electrodeposits, found that after long times the reaction front position was given by the power law P D * t 0.5 .…”
Section: Damkohler Numberda and 125mentioning
confidence: 99%